1998
DOI: 10.1046/j.1365-3083.1998.00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Bronchus‐Associated Lymphoid Tissue (BALT) and Larynx‐Associated Lymphoid Tissue (LALT) are Found at Different Frequencies in Children, Adolescents and Adults

Abstract: The lung in 98 and the larynx in 51 consecutive autopsies (age: 17th gestational week to 99 years) were studied for the presence of organized lymphoid tissue in the epiglottis and in the wall of larger bronchi. Bronchus-associated lymphoid tissue (BALT) was seen in about 40% of patients younger than 20 years of age but in older patients only in exceptional cases. In the wall of the epiglottis, however, larynx-associated lymphoid tissue (LALT) was found at a frequency of approximately 80% in patients younger th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(54 citation statements)
references
References 23 publications
1
50
1
2
Order By: Relevance
“…BALT is not constitutively present in farm animals and humans, but is very dynamic in these species [45,88]. It has been suggested that this is typical in species with a well developed Waldeyer's ring, while species with little lymphatic tissue at Waldeyer'ring, like mice, rats or rabbits, have constitutively large amounts of BALT [55].…”
Section: Bronchus-associated-lymphoid Tissue (Balt)mentioning
confidence: 99%
“…BALT is not constitutively present in farm animals and humans, but is very dynamic in these species [45,88]. It has been suggested that this is typical in species with a well developed Waldeyer's ring, while species with little lymphatic tissue at Waldeyer'ring, like mice, rats or rabbits, have constitutively large amounts of BALT [55].…”
Section: Bronchus-associated-lymphoid Tissue (Balt)mentioning
confidence: 99%
“…In a further series including lungs from adolescents and adults it became obvious that a certain proportion of human lungs contains BALT until the age of 20. As these lungs were obtained during autopsy in the legal medicine department, infection by specific lung pathogens cannot be excluded [23].…”
Section: Balt In the Lung Of Children And Adolescentsmentioning
confidence: 99%
“…However, studies in man [1][2][3] and animals [4,5] show that the larynx does contain immunological tissue. A minor part of this has been reported to be present in the form of epithelial follicles (larynx-associated lymphoid tissue: LALT [1]) in an age-and disease-dependent manner [1,6]. However, as with studies of gut [7] and trachea [8], the majority of immunologically active cells appear to be present in a more diffuse, although still organized manner [3,4].…”
Section: Introductionmentioning
confidence: 99%